Analisa Pola dan Sifat Aliran Fluida dengan Pemodelan Fisis dan Metode Automata Gas Kisi - Simon Sadok Siregar; Suryajaya Suryajaya; Muliawati Muliawatiq (Lambung Mangkurat University Press, 2010)
This research is conducted by using physical model and Lattice GasAutomata method for simple flow patterns having different geometry. Fromphysical model, the results are speed pattern and fluid flow permeability. Theresulted value of the permeability by using physical model will be compared tothe resulted value of the LGA. The compared value of the LGA method is thevalue with angle 5o, 10o and 15o by using laboratory scale. These angles arechosen due to it’s the lowest error compared to those of other angles. In thephysical model the lowest permeability value is gotten from the pattern of straightgeometry 60o with value 0.201 x 10-6 m2 and the highest permeability value isfrom pattern of turn 2 with value 0.341 x 10-6 m2. While by using LGA methodthe the lowest permeability value is pattern of straight 60o with value 0.209 x 10-6 m2 while the the highest real permeability value is pattern of turn 2 with value0.344 x 10-6 m2. From the comparison data of permeability the results of errorare 3.74%, 0.7% and 4.2% for the angle of 5o, 10o and 15o, respectively